Peningkatan Pengetahuan dan Kemampuan Keluarga dalam Merawat Lansia Melalui Penyuluhan dan Latihan Kemandirian Lansia di Kota Palembang - Ananingsih, Esti Sri; Amin, Maliha; Shobur, Sherly; Meilina, Meilina (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2019)
Elderly is part of the process of growth and development. The elderly experience physical decline and social changes that cause dependence on independence. Elderly who are used to having activities will be more independent than the elderly who are dependent. With physical changes, the elderly experience decreased hearing and vision, the mentally healthy elderly are the elderly who enjoy daily activities. If these needs can be met, then the fantasy arises to think and try to achieve how these needs can be met, for example food, clothing, shelter and health. The elderly is not to return to their role as breadwinners, but how to prepare them to be able to enjoy the last part of their lives with maximum independence. If the independence of helping oneself without assistance has been achieved, then there are still many areas of activity for the elderly that can still be explored and raised. In this regard, given the importance of the role of the family, the family must be even stronger in carrying out family duties, especially those related to the elderly. Through community service activities by providing counseling on elderly independence exercises, it is hoped that families can care for the elderly so that the elderly become independent and optimal in living life. This activity is aimed at families and the elderly who live in the area of RW 3 , 5 ilir Palembang in collaboration between Poltekkes Kemnekes Palembang Department of Nursing and the related Puskesmas